Root growth in sainfoin (Onobrychis viciifolia Scop.) submitted to different harvest times - De Giorgio D.; Maiorana M.; Fornaro F. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
On a permanent meadow of sainfoin (Onobrychis viciifolia Scop.), cropped under dry conditions, the effects of two harvest times (when plants reached, on the average, 10 and 20 cm of height) on the dynamic of root development have been evaluated, by means of the non destructive method of minirhizotrons. The research was carried out at Rutigliano (Southern Italy) from 1992 to 1994, using a miniature video camera. Measurements were taken during the legume vegetative cycle. Images were analysed and transformed in R.L.D. (Root Length Density) and the values so obtained were submitted to statistical analysis. The root growth varied according to harvest times: with the cut at 20 cm height, sainfoin mostly concentrated rooting intensity in the upper layer of the soil, while with the one at 10 cm there was a deeper root development, but with small growing intensity.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)